(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2025)
A study investigating microbial contamination in fresh produce sold in Bangladesh revealed significant levels of bacterial pathogens. Among 8 samples of tomatoes, carrots, cucumbers, and green peppers, high counts of total aerobic bacteria and enteric pathogens were detected. Staphylococcus aureus was identified in 75% of samples, with 100% prevalence in carrots and tomatoes. Escherichia coli was present in 62.5% of samples, predominantly in cucumbers (100%). Pseudomonas aeruginosa appeared in 62.5% of samples, while Vibrio sp. and Salmonella sp. were each detected in 50% of samples. Chopped-carrot samples exhibited the highest aerobic bacterial load, with 5.86 × 10⁴ CFU/g in winter (December–February) and 3.75 × 10⁴ CFU/g in summer (March–June). In contrast, chopped-tomato samples showed the lowest contamination, at 6.16 × 10³ CFU/g in winter and 1.65 × 10⁴ CFU/g in summer. Overall, bacterial contamination rates were elevated in summer and in chopped produce. The findings underscore the critical need for enhanced hygiene practices, rigorous monitoring, and improved handling protocols to ensure the safety of fresh produce in market settings. Bangladesh J. Sci. Ind. Res. 60(2), 115-124, 2025